Simplified Transient Hot-Wire Method for Effective Thermal Conductivity Measurement in Geo Materials: Microstructure and Saturation Effect - B. Merckx; P. Dudoignon; J. P. Garnier; D. Marchand (Advances in Civil Engineering)
The thermal conductivity measurement by a simplified transient hot-wire technique is applied to geomaterials in order to show the relationships which can exist between effective thermal conductivity, texture, and moisture of the materials. After a validation of the used “one hot-wire” technique in water, toluene, and glass-bead assemblages, the investigations were performed (1) in glass-bead assemblages of different diameters in dried, water, and acetone-saturated states in order to observe the role of grain sizes and saturation on the effective thermal conductivity, (2) in a compacted earth brick at different moisture states, and (3) in a lime-hemp concrete during 110 days following its manufacture. The lime-hemp concrete allows the measurements during the setting, desiccation and carbonation steps. The recorded Δ𝑇/ln(𝑡) diagrams allow the calculation of one effective thermal conductivity in the continuous and homogeneous fluids and two effective thermal conductivities in the heterogeneous solids. The first one measured in the short time acquisitions (<1 s) mainly depends on the contact between the wire and grains and thus microtexture and hydrated state of the material. The second one, measured for longer time acquisitions, characterizes the mean effective thermal conductivity of the material.